2006
DOI: 10.1681/asn.2005121305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Investigation of Autosomal Recessive Distal Renal Tubular Acidosis

Abstract: Mutations in the ATP6V1B1 and ATP6V0A4 genes, encoding subunits B1 and 4 of apical H ؉ ATPase, cause recessive forms of distal renal tubular acidosis (dRTA). ATP6V1B mutations have been associated with early sensorineural hearing loss (SNHL), whereas ATP6V0A4 mutations are classically associated with either late-onset SNHL or normal hearing. The phenotype and genotype of 39 new kindreds with recessive dRTA, 18 of whom were consanguineous, were assessed. Novel and known loss-of-function mutations were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 14 publications
8
109
1
4
Order By: Relevance
“…As the variation Intron 7−2 T>C has not been previously described, we corroborated pathogenicity by the Alternative Splice Site Predictor software, which revealed the base involved in a constitutive acceptor zone with a splice site strength score of 2.391 vs. 7.730 with the wild-type base. Patient 306 was carrying the mutation R394Q at the ATP6V1B1 gene (16) and also the variation E508K at the SLC4A1 gene with a predictive deleterious effect according to the PolyPhen software (value = 1) and of not safety by SIFT software (value = 0). To find out the way of segregation of both changes, we analyzed her parents who did not have the ATP6V1B1 gene mutation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the variation Intron 7−2 T>C has not been previously described, we corroborated pathogenicity by the Alternative Splice Site Predictor software, which revealed the base involved in a constitutive acceptor zone with a splice site strength score of 2.391 vs. 7.730 with the wild-type base. Patient 306 was carrying the mutation R394Q at the ATP6V1B1 gene (16) and also the variation E508K at the SLC4A1 gene with a predictive deleterious effect according to the PolyPhen software (value = 1) and of not safety by SIFT software (value = 0). To find out the way of segregation of both changes, we analyzed her parents who did not have the ATP6V1B1 gene mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, our series is too small to provide useful information on the relationship between the severity of hypokalemia and the underlying gene defect responsible for DRTA. Although the possibility of mutations occurring in a nonanalyzed regulatory element like promoters (28) or introns (16) or the existence of large rearrangements (24) undetected by these techniques cannot be excluded, the association of another gene involved in the renal regulation of acid-base equilibrium as responsible for DRTA cannot be ruled out. Sanger sequencing of ATP6V1B1, ATP6V0A4, and SLC4A1 does not disclose mutations in up to 20% of patients with clinical diagnosis of primary DRTA which supports the existence of other candidate genes as potentially responsible for a significant number of primary DRTA cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patient I-1 was a compound heterozygote with a recurrent duplication of c.1155dupC (p.Ile386Hisfs*56) 1,3,5,9 and a novel deletion of c.1356delT. This novel deletion led to a frameshift that resulted in premature termination of the protein at codon 486 (p.Phe452Leufs*35).…”
Section: Mutation Analysismentioning
confidence: 99%
“…A few cases harbored ATP6V1B1 mutations without SNHL have been described. 8,9 Recent genetic analyses have revealed that some individuals with mutations in the ATP6V0A4 gene also have early-onset severe SNHL. 9 And most recently, Andreucci et al described a child carrying ATP6V0A4 mutations with early profound SNHL and unexpected EVA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation